Impact of Climate Change on Water Factors in the Lower Chira and Piura River Basin - Chambi Echegaray, Gina (2023)
The Chira-Piura river basin is an essential supplier of water in northern Peru. Despite its nature and water capacity, the population is threatened by water shortages due to natural hazards. In 2023, Cyclone Yaku caused strong thermal gradients, altered the water factors, brought floods and affected the demand for water, which in these semi-arid regions is altered by climate change. The objectives of this research work are to develop conceptual tools for the study of the alteration of water variables in the Chira-Piura basin and their adverse effects in the face of more frequent and intense climatological phenomena. A non-experimental, cross-sectional, correlational, descriptive, descriptive design is used in a quantitative approach, with a comparative statistical analysis of hydrological and climatic parameters. Due to climate change, it is projected that the next events may be more intense and the El Niño phenomenon more frequent, affecting the usual rainfall and flow patterns. Challenges associated with flood prevention and future opportunities have been identified including the development of quality datasets and the inclusion of data assimilation techniques and hydrological modelling.